Drug Delivery: ATP‐Responsive Aptamer‐Based Metal–Organic Framework Nanoparticles (NMOFs) for the Controlled Release of Loads and Drugs (Adv. Funct. Mater. 37/2017). (4th October 2017) - Chen, Wei‐Hai; Yu, Xu; Liao, Wei‐Ching; Sohn, Yang Sung; Cecconello, Alessandro; Kozell, Anna; Nechushtai, Rachel; Willner, Itamar
Abstract : Aptamer‐capped, drug‐loaded metal‐organic framework nanoparticles (NOMFs) are synthesized by a click chemistry method by Itamar Willner and co‐workers in article number1702102 . The NOMFs are unlocked by ATP, which is overexpressed in cancer cells, leading to high cytotoxic efficacy and targeted drug release to MDA‐MB‐231 breast cancer cells.